2020
DOI: 10.1097/gox.0000000000003312
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Secondary Surgeries after Immediate Breast Reconstruction for Cancer Compared with Risk Reduction

Abstract: Background: This study sets out to compare reconstructive practice between patients undergoing immediate breast reconstruction (IBR) for cancer and those who opted for risk reduction (RR), with an emphasis on examining patterns of secondary surgery. Methods: Data collection was performed for patients undergoing mastectomy and IBR at a teaching hospital breast unit (2013–2016). Results: In total, 299 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 30 publications
4
6
0
Order By: Relevance
“…We agree with the assertions of Jones et al that immediate BRs should not be seen or sold to patients as a 'one off procedure', and suggest that all patients should be counselled as to the need for potential revisions in the future. 10 The associations found between smoking and revision surgery are consistent with current scientific understanding of the higher risk of post-operative complications caused by smoking. 17,18 A higher risk of complications will thereby increase the risk of requiring revision surgery.…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…We agree with the assertions of Jones et al that immediate BRs should not be seen or sold to patients as a 'one off procedure', and suggest that all patients should be counselled as to the need for potential revisions in the future. 10 The associations found between smoking and revision surgery are consistent with current scientific understanding of the higher risk of post-operative complications caused by smoking. 17,18 A higher risk of complications will thereby increase the risk of requiring revision surgery.…”
Section: Discussionsupporting
confidence: 81%
“…Also, a study by Jones et al, investigating secondary surgeries in BR, found an unplanned secondary surgery rate of 28% in patients having a reconstruction for cancer and 25% in patients having risk reducing surgery. 10 These rates are across all types of reconstruction.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations